Comparative evaluation on the effect of different cavity disinfectant nano gels; Chlorohexidine, Propolis, Liquorice versus Diode Laser in terms of composite microleakage (comparative in vitro study) - Maryam Mohamed ElMansy; Silvia Sabry Tawfik Tadros; Reham Sayed Saleh; Rehab Abdelmonem; Hala El Menoufy; Naglaa Shawky (Nature Publishing Group, 2023)
Abstract Introduction The application of different cavity disinfectants is an essential step that eliminates bacteria after cavity preparation. However, some of these materials may affect restoration sealing ability. Aim This study aimed to assess the degree of microleakage at the tooth restoration interface after using different nano prepared cavity disinfectants versus Diode Laser. Materials and methods Three disinfectants were prepared on the nanoscale; Propolis, Liquorice and Chlorhexidine. A total of 40 extracted premolars with standard class V cavities were prepared on the facial surface. Teeth were divided into five groups according to the applied cavity disinfection protocol; no treatment, Chloehexidine, Propolis, Liquorice, and Diode Laser. After application of composite resin restoration, all teeth were subjected to thermocycling, afterwords the degree of microleakage was measured in micrometers. Data were analyzed by one-way analysis of variance (ANOVA) test, followed by Bonferroni's and Tukey's post hoc test. Results The highest mean microlekage value was recorded in no treatment group, followed by Liquorice, Propolis. While Diode Laser group showed the lowest degree of microleakage. Conclusion Diode Laser cavity disinfectant has no negative effect on the restoration sealing ability. Nano prepared Propolis showed comparative results to nanoChloehexidine as both had low degree of microleakage.